Pareto Inefficient Horizontal Mergers in Mixed Oligopolies - Flavio Delbono; Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
In this paper we analyze horizontal mergers in mixed oligopolies. We first consider a mixed duopoly where the merger creates a monopoly, and we distinguish two cases.
Keywords: 330